Corrigendum to “Augmented reality marker-based technology for augmenting newspaper advertisement" - Pervez, Rahat; Chowdhury, Diba; Sagor, Md. Sahadat Hossain; Hoque, Md. Imdadul; Islam, Nafiul (Recent Research in Science and Technology, 2022)
Recent Research in Science and Technology, 2021, 13, 13–18. https://doi.org/10.25081/rrst.2021.13.7005 One of the authors’ (Md. Imdadul Hoque3) affiliations was mentioned incorrectly. It should be read as follows: 3Department of Computer Science and Telecommunication Engineering, Noakhali Science and Technology University, Noakhali – 3814, Bangladesh